1998
DOI: 10.1046/j.1365-3156.1998.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ivermectin on onchocercal skin disease and severe itching: results of a multicentre trial

Abstract: Summaryobjective To determine the effects of ivermectin in annual, 3-monthly and 6-monthly doses on onchocercal skin disease (OSD) and severe itching.method A multicentre, double-blind placebo controlled trial was conducted among 4072 residents of rural communities in Ghana, Nigeria and Uganda. Baseline clinical examination categorized reactive skin lesions as acute papular onchodermatitis, chronic papular onchodermatitis and lichenified onchodermatitis. Presence and severity of itching was determined by open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 20 publications
(28 reference statements)
4
43
1
1
Order By: Relevance
“…Hence, we applied a relationship between the prevalence of troublesome itch and of adult female worms, previously derived using ONCHOSIM [25,26]. Troublesome itch was related to the presence of female adult worms because the association between the presence of mf and troublesome itch does not hold during ivermectin treatment, the reduction in prevalence of itch being smaller and more delayed than the drop in microfilarial prevalence and load [25,26,53]. This relationship is subject to considerable uncertainty and so it was varied in the sensitivity analysis (Table  3).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we applied a relationship between the prevalence of troublesome itch and of adult female worms, previously derived using ONCHOSIM [25,26]. Troublesome itch was related to the presence of female adult worms because the association between the presence of mf and troublesome itch does not hold during ivermectin treatment, the reduction in prevalence of itch being smaller and more delayed than the drop in microfilarial prevalence and load [25,26,53]. This relationship is subject to considerable uncertainty and so it was varied in the sensitivity analysis (Table  3).…”
Section: Methodsmentioning
confidence: 99%
“…Now that the importance of skin disease had been demonstrated, there was a need to further clarify the effectiveness of ivermectin treatment in OSD and to determine the most appropriate treatment interval as it had been suggested that annual treatment might not be adequate for OSD and that treatment may need to be given as often as every 3 months (Burnham 1995). A multicentre double-blind placebo-controlled trial was undertaken, which showed that ivermectin treatment resulted in a significant reduction in itching and reactive skin lesions during the first year after treatment and that there was no difference between 3-monthly, 6-monthly and annual treatment regimens (Brieger et al 1998a). Hence, the annual treatment regimen was accepted for all endemic areas, including those with the 'forest' strain of the parasite.…”
Section: Apoc: Expansion Of Control To All Endemic Countries In Africamentioning
confidence: 99%
“…2,3 The impact of onchocercal skin disease on both the health of infected individuals and on the economy of the local communities is significant. 1,[3][4][5][6] In addition, onchocercal skin disease is a focus of the African Program for Onchocerciasis Control. 3,4 In the current study, we used a murine model that reproduces clinical and histologic features of early stage onchocercal skin disease to examine underlying pathogenic mechanisms.…”
mentioning
confidence: 99%